Examination of Interpenetrating Polymer Networks of Polyurea in Silicone Molds Arising during Vacuum Casting Processes. Issue 15 (13th October 2018) - Wortmann, Martin; Frese, Natalie; Heide, Alexander; Brikmann, Johannes; Strube, Oliver; Dalpke, Raphael; Gölzhäuser, Armin; Moritzer, Elmar; Hüsgen, Bruno
ABSTRACT: We present an in-depth investigation of the aging effects in silicone molds for vacuum casting processes. Their lifetime is limited to a few production cycles due to contamination with the diisocyanate component of polyurethane casting materials. Using thermogravimetric analysis measurements, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and helium-ion-microscopy the chemical and physical mechanisms of the aging process have been identified. It has been shown that a diffusion process of diisocyanate into the cavity surface leads to the formation of interpenetrating polymer networks of polyurea derivatives in silicone rubber. This has been proven by extracting and analyzing polyurea of low molecular weights from the silicone. GRAPHICAL ABSTRACT: